ANTI-ULCER POTENTIAL CHLOROFORM EXTRACT OF CUCUMIS SATIVUS - Singh, Charanjeet; Gujar, Bhojraj; Sharma, Yogesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2019)
Ulcers are lesions on the surface of the skin or a mucous membrane characterized by a superficial loss of tissue. Helicobacter pylori is uniquely adapted to survival in the hostile environment of stomach. C. sativus is hairy and the root system is extensive and superficial. Leaves are alternate and simple. Flowers are yellow regular and unisexual. The matured fruit is about 30 cm long, roughly cylindrical and often slightly curved. The dried fruit of Cucumis sativus were collected from local area of Alwar, Rajasthan. Dried fruit of C. sativus were cut in to small pieces and dried under the shade. Water and alcoholic soluble extractive value of C. sativus was determined. 4.0 g fruits powder of C. sativus was weighed individually and macerated with distilled water (100 ml) in a glass-stopperd conical flask for 24 hours. Total ash, water soluble ash, acid insoluble ash and sulfated ash value of C. sativus was determined. 200 g coarse fruits powdered fruits were defatted with 800 ml petroleum ether (60-800C) using soxhlet apparatus. Phytochemical screening of C. sativus extracts were carried out on the basis of qualitative chemical tests and TLC. Evaluation of anti-ulcer activity of C. sativus fruits by Acute toxicity method and ulcer index was calculated, the percentage yield of petroleum ether, chloroform and extract of C. sativus fruits was found to be 6.35 %, 7.26 % respectively. All these observation imply that the Chloroform extract of fruits of C.sativus could be regarded as a favourable antiulcerogen which could be attributed to its content of flavonoids and mucilage. Keywords: Ulcers, Cucumis sativus, flavonoids, mucilage.